Heterogeneity in the distribution of health professionals in Brazil and the Covid-19 pandemic - dos Santos, Anselmo Luís; Manzano, Marcelo; Krein, André (Cadernos do Desenvolvimento, 2023)
The paper analyses the distribution of health professionals in Brazil and its implications for the fight against COVID-19. On the one hand, it stresses that disparities in the regional distribution of health professionals is one of the most worrisome aspects of the national health system current structure. On the other hand, it argues that thanks to the extent and decentralization of the Unified Health System, those disparities are partly mitigated by the public network, compensating the relative scarcity of private health services in lower per capita income states. It is observed that in the face of the risks of health care activities related to the pandemic conjuncture, the extended working hours and the incidence of Covid-19 cases among health professionals occurred mostly among mid-level workers, revealing greater risks and insecurity among those with more precarious and lower-paid occupations.